Faktor-Faktor yang Menyebabkan Indikator Pendukung dan Tantangan Ketidakefektifan Pendistrbusian Gas LPG 3 Kg Bersubsidi di Kelurahan Gates Nan XX Kota Padang - Putri, Silvina Maharani; Eriyanti, Fitri (Al-DYAS, 2025)
The distribution of subsidized 3-kg LPG is a critical aspect in ensuring the targeted allocation of energy subsidies, particularly for low-income households and micro-enterprises. In Gates Nan XX Village, Padang City, the implementation of 3-kg LPG distribution faces several obstacles that hinder the program’s effectiveness, including limited supply quotas, inaccurate recipient data, and weak price monitoring at the retail level. This study aims to analyze and identify the supporting and inhibiting factors in the implementation of subsidized 3-kg LPG distribution at the Village level. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. Informants included the Village head, neighborhood and community leaders (RT/RW), LPG agents and base owners, as well as subsidy recipients and micro-entrepreneurs. The findings indicate that the distribution of 3-kg LPG in Gates Nan XX Village has not been optimal. Although mechanisms such as data collection based on the Integrated Social Welfare Data (Data Terpadu Kesejahteraan Sosial), purchase limits at distribution points, and coordination among local officials and RT/RW have been implemented, issues such as supply delays, long queues, prices exceeding the official retail price ceiling (Harga Eceran Tertinggi, HET), and misuse by ineligible parties persist. The main inhibiting factors include limited supply quotas, weak data updating mechanisms, ineffective price supervision, and low public awareness. This study provides empirical insights into the local-level implementation of LPG subsidy policy and recommends improvements in distribution governance to ensure more accurate, equitable, and sustainable outcomes.